RESEARCH OF THE AERODYNAMIC MODE OF THE DRYER DRUM OF THE CLEANING SECTION (American Journal of Pedagogical and Educational Research, 2024)
The article gives the results of a theoretical study of the aerodynamic regime of pneumatic systems, providing a combination of drying and cleaning processes in cotton dryer drums, increasing the cleaning effect on fine litter and dust.The movement of two phases (debris and air) into the systems for removing contaminated air from the drying chamber was studied.The main task was to determine the angle of curvature of the pipe of the main channel, as well as other mechanical and geometric shapes of the side channels and flow.A scheme has been drawn up for the development of analytical formulas for determining the hydroaerodynamic and other parameters of a mixture of litter and air.When solving the problem, to ensure the uniformity of the distribution of litter and air in the channels, use the theory of a complex variable.Formulas for determining the geometric dimensions of pneumatic pipes are obtained.